5, 6-dehydrokawain from the rhizome of Alpinia mutica Roxb. induced proangiogenic tumour-derived VEGF of HT-29 colorectal cancer. Issue 24 (17th December 2018) - Malami, Ibrahim; Muhammad, Aliyu; Abubakar, Ibrahim B.; Etti, Imaobong C.; Waziri, Peter M.; Abubakar, Ramadan M.; Mshelia, Halilu E.
Abstract: Vascular endothelial growth factor (VEGF) is a glycoprotein vital to the regulation of vascular endothelial cells proliferation, migration and angiogenesis. The expression of VEGF is required for the formation of new blood vessels critical in supplying oxygen and nutrition in the course of tumorigenesis. The present study investigated the effect of 5, 6-dehydrokawain isolated from the rhizomes of Alpinia mutica on VEGF expression in vitro using HT-29 cell line. The results revealed that 5, 6-dehydrokawain induced the expression of proangiogenic tumour-derived VEGF of HT-29 cells, which may explain the inability of 5, 6-dehydrokawain in suppressing cancer cells proliferation. Abstract :